PARTIAL RENAL FUNCTIONS AND FLUID-AND-ELECTROLYTE BALANCE IN EXPERIMENTAL FLUOROSIS - Ядыкина, Татьяна Константиновна; Горохова, Лариса Геннадьевна; Корсакова, Татьяна Георгиевна (Medicine in Kuzbass, 2017)
Objective. The study on the changes in the fluid-and-electrolyte balance of the body and partial renal functions in the dynamics of the development of experimental fluorosis.Materials and methods. The survey of the biochemical indices of blood plasma and urine in 1, 3, 6, 9, 12 weeks of the experiment was carried out. The changes in the level of fluorine, sodium, potassium, total protein, calcium, inorganic phosphorus, urea, creatinine, parathyroid hormone was studied. Diurnal diuresis was determined by the metrical way in the exchange cells for rats. The partial renal functions were calculated.Results. An experimental study on the changes in morphofunctional activity of the kidneys and physiological mechanisms aimed at maintaining homeostasis under the conditions of prolonged exposure to sodium fluoride was carried out. It was shown that up to the 6th week the preservation of the constancy of the parameters of the internal body environment was ensured by the intensity of the filtration-reabsorption processes and the maintenance of the hydroionic balance at a relatively stable level with the formation of a «toxic kidney» by the end of the experiment (12 weeks).Conclusions. The experiment showed that the prolonged exposure to sodium fluoride on the body was accompanied by the development of chronic nephropathy against the persistent disorders of the fluid-and-electrolyte balance and irreversible degenerative-dystrophic changes in the renal parenchyma.
Keywords: fluorine; kidneys; fluid-and-electrolyte balance; homeostasis; fluorosis